Peran Teknologi Informasi dan Komunikasi dalam Kehidupan Modern serta Dampaknya terhadap Dunia Pendidikan - Youris Pratama Djeri Yunanta; Adi Nugroho; M. Abyan Al Irsyad; Rifqy Tombak Matahari; Dimas Pramodya Dwipayana (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The development of Information and Communication Technology (ICT) has significantly impacted many aspects of life, including education. Digital innovations and internet access have facilitated information retrieval and communication, while also fostering more interactive, flexible, and creative learning experiences through digital media and virtual learning. However, the use of ICT also presents challenges, such as technological dependency, internet misuse, and disparities in access across certain regions. This article aims to explore the role of ICT in contemporary life and its positive and negative effects on education. Based on a literature review, the findings indicate that ICT enhances the quality of education and access to information. Nevertheless, the utilization of ICT must be balanced with digital literacy and adequate supervision to ensure its benefits are fully realized.